A guide to assessments that work - Hunsley, John, 1959-; Mash, Eric J. (New York : Oxford University Press, 2008)
The need for evidence-based practice in mental health services is becoming clearer by the day and, until recently, the trend of emphasizing services with supporting empirical evidence has been almost exclusively limited to a focus on treatment options. A Guide to Assessments That Work fills a void in the professional literature by addressing the critical role that assessment plays in providing evidence-based mental health services. To optimize its usefulness to readers, this volume addresses the assessment of the most commonly encountered disorders or conditions among children, adolescents, ad.
Table of Contents; Contributor List; Preface; Foreword; Part I: Introduction; Part II: Attention-Deficit and Disruptive Behavior Disorders; Part III: Mood Disorders and Self-Injury; Part IV: Anxiety Disorders; Part V: Substance Use and Gambling Disorders; Part VI: Schizophrenia and Personality Disorders; Part VII: Couple Distress and Sexual Problems; Part VIII: Health-Related Problems; Assessment Instrument Index; Author Index; Subject Index.
Includes bibliographical references and indexes.
Print version record.
WorldCat record variable field(s) change: 650
Keywords: Psychodiagnostics; Evidence-based psychiatry; Evidence-based medicine; Mental Disorders -- diagnosis; Evidence-Based Medicine; Psychodiagnostics; Psychiatrie factuelle; Médecine factuelle; MEDICAL -- Psychiatry -- General; PSYCHOLOGY -- Psychopathology -- General; PSYCHOLOGY -- Clinical Psychology; PSYCHOLOGY -- Mental Illness; MEDICAL -- Mental Health; Evidence-based psychiatry; Psychodiagnostics; Klinische psychologie; Psychodiagnostiek; Evidence-based practice; Electronic books; Electronic books